Richard J. Bernstein and the Pragmatist Turn in Contemporary Philosophy
X, 234 p.
Keywords: Richard J. Bernstein, who has played a leading role in "the pragmatist turn" in contemporary philosophy, replies to twelve younger critics in a lively conversation about pragmatism's past, present, and future as a guiding paradigm for philosophy and related fields.